The cleansing effect of banking crises - Reint Gropp; Steven Ongena; Jörg Rocholl; Vahid Saadi (Halle Institute for Economic Research (IWH), 2020)
We assess the cleansing effects of the recent banking crisis. In U.S. regions with higher levels of supervisory forbearance on distressed banks during the crisis, there is less restructuring in the real sector and the banking sector remains less healthy for several years after the crisis. Regions with less supervisory forbearance experience higher productivity growth after the crisis with more firm entries, job creation, and employment, wages, patents, and output growth. Supervisory forbearance is greater for state-chartered banks and in regions with weaker banking competition and more independent banks, while recapitalisation of distressed banks through TARP does not facilitate cleansing.
urn:nbn:de:101:1-2020071511032570392902
Keywords: G01; G21; G28; O43; 330; cleansing effect; banking crises; supervisory for bearance; productivity growth